Manjo-manjo Dance in the Social Life of the Padang Peri Community, Semidang Alas Maras District, Seluma Regency - Sapitri, Widia Mayang; Hakim, Ramalis (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2022)
this study aimed to describe the dance manjo-manjo in the social life of Padang Peri at wedding ceremonies. This study focused on presenting manjo-manjo dance, the functions and meaning of the dance in the social life of the Padang Peri community. This type of research is qualitative research with a descriptive method. The data collection technique was done using library research, observation, interviews, and documentation techniques. The research instrument was the researcher herself as the key instrument. The research location was in the village of Padang Peri, Semidang Alas Maras District, Seluma Regency. Techniques for checking the validity of the data were the extension of participation, the persistence of observers, triangulation. The steps to analyze the data were data reduction, data presentation, and concluding (verification). Data analysis was carried out using the Miles and Huberman technique. The results showed that the form of presentation of the manjo-manjo dance was a traditional dance with three movements of ngebar hand, nyengkeling, and fluttering (ngipas). The function of the dance manjo-manjo is as a traditional wedding ceremony and as entertainment. In contrast, the meaning of the dance manjo-manjo is a forum for friendship and getting to know each other between the two happy families and the people. Therefore, they are present at the wedding reception ceremony. The meaning of the manjo-manjo dance can be seen from the three movements. The first is the spread of the hands. It means a welcome greeting, especially to the bride and her family. The second movement, nyengkeling, means the acceptance of the bride and her family into a new family from the groom's side. Finally, the last movement is fanning. It is a sign of peace and hope the two families are in harmony.